Long-Term Outcomes of Treosulfan- vs. Busulfan-Based Conditioning Regimen for Patients With Myelodysplastic Syndrome and Acute Myeloid Leukemia Before Hematopoietic Cell Transplantation: A Systematic Review and Meta-Analysis - Zhu, Sheng; Liu, Gang; Liu, Jing; Zhang, Shuixing; Chen, Qiuying; Wang, Zhiqiang (Frontiers in Oncology, 2020)
Background Many studies aimed to evaluate the efficacy and safety of treosulfan-based conditioning regimens for allogeneic hematopoietic cell transplantation (allo-HCT) compared with other regimens, but different outcomes were reported across studies. Aim To determine the long-term survival outcomes of treosulfan-based vs. busulfan-based conditioning regimens in myelodysplastic syndrome (MDS)/acute myeloid leukemia (AML) patients. Methods PubMed, Embase, and Cochrane library, were searched for studies published prior to December 6, 2019. The fixed-effects model was applied for overall survival (OS), leukemia-free survival (LFS), non-relapse mortality (NRM), acute and chronic graft versus host disease (GvHD). Relapse incidence (RI) was pooled by the use of the random-effects model. Results Six studies were included (3982 patients; range, 57-1956). The pooled HR for OS favored treosulfan (HR=0.80, 95%CI: 0.71-0.90). There was no significant difference in NRM between the two regimens (HR=0.84, 95%CI=0.71-1.01). There was no significant difference in LFS between the two regimens (HR=0.98, 95%CI=0.87-1.12). Treosulfan-based regimens showed a lower risk of aGvHD (HR=0.70, 95%CI=0.59-0.82), but there was no difference for cGvHD (HR=0.94, 95%CI=0.81-1.09). There was no significant difference in RI between the two regimens (HR=0.96, 95%CI=0.71-1.31). There was no publication bias among these studies. Conclusion The current meta-analysis determined that treosulfan-based conditioning regimens could improve the OS in patients with MDS and AML, with lower acute graft-versus-host disease incidence, compared with busulfan-based regimens.